A Field-Based Approach to Determine Soft Tissue Injury Risk in Elite Futsal Using Novel Machine Learning Techniques - Ruiz-Pérez, Iñaki; López-Valenciano, Alejandro; Hernández-Sánchez, Sergio; Puerta-Callejón, José M.; De Ste Croix, Mark; Sainz de Baranda, Pilar; Ayala, Francisco (Frontiers in Psychology, 2021)
Lower extremity non-contact soft tissue (LE-ST) injuries are prevalent in elite futsal. The purpose of this study was to analyze and compare the individual and combined ability of several measures obtained from questionnaires and field-based tests to prospectively predict LE-ST injuries after having applied a range of supervised Machine Learning techniques. One hundred and thirty-nine elite futsal players underwent a pre-season screening evaluation that included individual characteristics; measures related to sleep quality, athlete burnout, psychological characteristics related to sport performance and self-reported perception of chronic ankle instability. A number of neuromuscular performance measures obtained through three field-based tests (isometric hip strength, dynamic postural control [Y-Balance] and lower extremity joints range of motion [ROM-Sport battery]) were also recorded. Injury incidence was monitored over one competitive season. There were 25 LE-ST injuries. Only those groups of measures from two of the field-based tests (ROM-Sport battery and Y-Balance), as independent data sets, were able to build robust models (area under the receiver operating characteristic curve [AUC] score ≥ 0.7) to identify elite futsal players at risk of sustaining a LE-ST injury. Unlike the measures obtained from the five questionnaires selected, the neuromuscular performance measures did build robust prediction models (AUC score ≥ 0.7). The inclusion in the same data set of the measures recorded from all the questionnaires and field-based tests did not result in models with significantly higher performance scores. The models developed might help coaches, physical trainers and medical practitioners in the decision-making process for injury prevention in futsal.